W stronę hermeneutyki postantropocentrycznej - Szaj, Patryk (Zoophilologica. Polish Journal of Animal Studies, 2020)
The author of the article asks whether it is possible to practice post-anthropocentric hermeneutics. He expresses the need for opening the hermeneutic thought to the problem of what is non-human, especially in the context of contemporary diagnoses of the Anthropocene, climate crisis, ecological crisis, etc. Such a postanthropocentric correction of hermeneutics is possible due to the notion of “understanding” which can be extended towards understanding of non-human others and towards understanding with non-human others. This coincides with insights which have been formulated within animal studies, ecocriticism, posthumanism, etc. In order to make such an extension happen, however, a biopolitical correction of hermeneutics is also required, which would restore the hermeneutic subject to the biological and material life.